(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Despite the fact that many researches have been conducted on the disease of diabetes mellitus (DM), this pathology remains one of the global problems of medicine. Statistics show that patients with diabetes have a high rate of anemia. The purpose of our research is to determine changes in the hemoglobin index in general blood tests in patients with type 2 diabetes.